Proposal for an evaluation scale of executive functions in university students - López-Cárdenas, María (2021)
Introduction. The executive functions constitute a set of cognitive, affective and motivational processes, which allow the conscious control of thought, development of highly complex tasks, that is going to facilitate the adaptation to new situations, it is therefore necessary the contribution of new evaluation methodologies of executive functions centered on the university population, this is going to facilitate the access to check the cognitive processes of the pre-frontal cortex. Objective. Evaluate executive functions in university students between 18 and 25 years of age using a self-report scale. Subjects and method. 752 university students from Quito-Ecuador participated, aged between 18 and 25 years old, of whom 498 (66.2%) were female and 254 (33.8%) were male. As measuring reagent, the scale used to evaluate the executive functions in self-report was proposed in the project: Neuropsychological Systems for Supervision of Cognition and Behavior for the Benefit of Managing the Learning of Higher Education Students. Results. Exploratory factor analysis reported an organization of 8 executive functions that explain 57% of the variance of the construct (p = <.001). An adequate level of reliability was obtained between α =.70 and.86, a factor was eliminated since its level of reliability was very low and did not improve under any statistical procedure. The correlation between the proposed factors was adequate at a median magnitude r =.67 and.39. Conclusion. The results show that the proposed scale is based on situations in the student's daily life, this scale design allows identifying both pathological situations and conditions that affect the quality of life and development in the university environment. Furthermore, psychometric indicators provide evidence in favor of their reliable use in the university context.